Sistem Informasi Geografis Rumah Makan Padang Di Kota Bogor Berbasis MobileGis - Alamsyah, Fahmi (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
Padang Restaurant (RM) or Warung Padang or Padang Restaurant is a food stall / restaurant / restaurant business that sells or serves a variety of Minangkabau culinary or cuisine originating from West Sumatra. With high mobility and technological advancements in this era will encourage people to want easy things in realizing their needs, one is looking for a Padang-eating house. Therefore, this research was built to create a Mobilegis-based Padang restaurant application using the location based service method and formula haversine formula that aims to facilitate Android smartphone users in finding and choosing the nearest Padang restaurant from the user's position and according to their choice. The system design used is the adaptive model method which includes the process activity phase which consists of scope, design, build, test and check presented in separate stages such as requirement specifications, software design, implementation, testing, etc. In the application the user is facilitated with there is a route feature that will guide to the Padang restaurant that has been previously selected. Conclusion What was obtained from this study was the result of the distribution of the Padang restaurant in the city of Bogor, the results of the analysis for calculating the distance of the nearest Padang restaurant using haversine. The results of the implementation of the distribution of Padang restaurants in the city of Bogor based on mobilegis.